Prognostic Significance of NLR, PLR, LMR and Tumor Infiltrating T Lymphocytes in Patients Undergoing Surgical Resection for Hilar Cholangiocarcinoma - Lin, Zhi-qiang; Ma, Chi; Cao, Wen-zhuo; Ning, Zhen; Tan, Guang (Frontiers in Oncology, 2022)
Objective: This study evaluated the prognostic significance of preoperative neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR) and tumor-infiltrating lymphocytes (TILs), and whether these preoperative blood inflammatory indicators were associated with TILs in hilar cholangiocarcinoma (HCCA). Methods: A total of 76 patients with HCCA who underwent radical resection were included. Data on their clinicopathologic characteristics, perioperative features, and survival outcomes were analyzed. The optimal cutoff levels for the NLR, PLR and LMR were defined by using the web application Cut-off Finder. The densities of specific immune cells (CD3+, CD4+, CD8+) within the tumor microenvironment were examined by immunohistochemical. The association of the number of CD3+, CD4+ and CD8+ T cells infiltration in the local tumor microenvironment with preoperative NLR, PLR and LMR level was analyzed. Survival curves were calculated using the Kaplan–Meier estimate. Univariate and multivariate logistic regression models were used to identify factors associated with overall survival. Results: The optimal cutoff value of preoperative NLR, PLR and LMR was 2.00, 117.60, and 4.02, respectively. NLR was significantly negatively correlated with CD3+ and CD8+ T cell infiltration, but not with CD4+ T cells. PLR had no correlation with CD3+, CD4+, or CD8+ T cell infiltration, while LMR had a significantly positive correlation with CD3+ T cells infiltration but not with CD4+ or CD8+ T cells. In the multivariate logistic regression model, T stage, lymph node metastasis, CA19-9 and LMR were independent risk factors associated with overall survival (OS). Survival curves indicated that HCCA patients with low CD3+ T cells infiltration and low preoperative LMR live shorter than others. Conclusions: LMR played as an independent factor for predicting the survival in patients with HCCA after R0 radical resection. A high LMR was associated with an accumulation of CD3+ T cells in HCCA. Keywords: hilar cholangiocarcinoma, NLR, PLR, LMR, tumor-infiltrating lymphocytes